Rapid alterations in the levels of bombesin-like peptides and their receptors in response to a single meal. - Kateb, Claude Christian. (University of Ottawa (Canada), 1993)
It has been suggested that bombesin (BN)-like peptides may play a physiological role in the control of food intake. The working hypothesis behind the experiments presented in this dissertation was that if this family of peptides is involved in the mediation of satiety, then the availability of the peptide(s) and/or its receptors should change with feeding status. Thus, the specific objectives of this research were to elucidate the changes in the availability of central and peripheral BN-like peptides and their receptors during a meal. In our preliminary experiments, all rats were food deprived for a 12 hr period. Half the animals were then permitted to eat solid food until satiated (35 min). Techniques of Radioimmunoassay (RIA) and quantitative autoradiography (QAR) were employed to measure peptide and receptor levels respectively in several brain and gut sites. Our results indicated significant increases in BN-like peptide levels, specifically gastrin-releasing peptide (GRP) GRP1-27 and/or GRP18-27, in the hypothalamus, hippocampus, and antral region of the stomach after food ingestion. The autoradiography study indicated an effect of food intake on central, but not gastrointestinal, BN-like peptide receptors, but failed to identify specific loci where these differences were significant between feeding states. The objective of the next series of experiments was to elucidate the pattern and degree of change in the levels of BN-like peptides and their receptors at different timepoints during different feeding states. These experiments included four groups of animals: (1) Rats that were food deprived for a 12 hr period; (2) and then given access to food for either 10 min or (3) 35 min. The fourth group constituted of non-deprived controls (ad libitum fed). RIA of hypothalamic, hippocampal, and medullary (control) tissues replicated and extended our earlier findings and showed that, in relation to the ad libitum condition, hypothalamic BN-like peptide concentrations were reduced by fasting, while hippocampal levels were elevated by feeding. The autoradiographic studies of several central areas demonstrated decreased binding in the hypothalamus, fundus striatum, and nucleus accumbens of the postprandial animals, as compared to the food deprived group. In the next experiment, an attempt was made to identify whether the changes noted at the receptor level were related to changes in the receptor number or affinity. The saturation experiments did not reveal significant alterations in the KD and Bmax of BN-like peptide receptors in response to food intake. Thus, the mechanisms underlying these receptor changes were not successfully established. The rapid alterations in peptide and receptor levels may support the contention that BN-like peptides play a physiological role in the regulation of ingestive behavior.
Keywords: Biology, Animal Physiology.